2019
DOI: 10.1080/19434472.2019.1698634
|View full text |Cite
|
Sign up to set email alerts
|

Fighting terrorism in Africa when existing terrorism levels matter

Abstract: This study examines policy tools in the fight against terrorism when existing levels of terrorism matter in 53 African countries for the period 1998-2012. The empirical evidence is based on contemporary, non-contemporary and Instrumental Variable Quantile regressions (QR) which enable the investigation throughout the conditional distributions of domestic, transnational and total terrorism dynamics. The following findings are established. First, counterterrorism policy instruments of inclusive human development… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 108 publications
0
1
0
Order By: Relevance
“…This is also in line with previous studies on terrorism where a priori expectations failed to hold. For instance, Asongu et al (2019) found a positive relationship between inclusive development and terrorism. This finding supports our conclusion that inequality reduces terrorism, as inclusive development is necessary for terrorism to persist.…”
Section: Discussionmentioning
confidence: 99%
“…This is also in line with previous studies on terrorism where a priori expectations failed to hold. For instance, Asongu et al (2019) found a positive relationship between inclusive development and terrorism. This finding supports our conclusion that inequality reduces terrorism, as inclusive development is necessary for terrorism to persist.…”
Section: Discussionmentioning
confidence: 99%